A MODEL OF COOPETITIVE GAME FOR THE ENVIRONMENTAL SUSTAINABILITY OF A GLOBAL GREEN ECONOMY - CARFI, David; SCHILIRO, Daniele (Journal of Environmental Management and Tourism; Vol 3 No 1 (2012): JEMT Volume III Issue 1(5) Summer 2012, 2016)
The present paper provides a model of coopetitive game for environmental sustainability of a global green economy, looking for a win-win solution within a complex construct of a type originally devised by Branderburger and Nalebuff. The model here suggested is environmental sustainable since it should lead to maintain natural capital, by using mainly renewable resources. In addition, this model of coopetitive games for environmental sustainability aims at reducing emissions of greenhouse gases, determining the reduction of global pollution, in this way it contributes to the establishment of a sustainable and lasting global green economy. Finally, the model determines a change in the patterns of consumption of households towards goods and human behaviors with a lower environmental impact. So the coopetitive strategy, in our model, consists in implementing a set of policy decisions, whose purpose is to be environmental sustainable and to enforce the global green economy. This is why the coopetitive variable is represented by a set of variables that together guarantee the achievement of the environmental sustainability of a global green economy. Thus, this original model aims to enrich the set of tools for environmental policies.
Keywords: coopetitive games; environmental sustainability; global green economy